2006 2nd International Conference on Information &Amp; Communication Technologies
DOI: 10.1109/ictta.2006.1684436
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Design of Scenarios for a Didactic-based E-learning System viewed as an Adaptive Virtual Document

Abstract: The design and engineering of E-learning systems must be considered as a transdisciplinary problem requiring the integration of different scientific approaches. The design process of E-learning systems needs to consider several theories, models and artifacts-the e-learning system. We claim it is essential to ensure the traceability and the interpretation of phenomena related to the use of artifacts in studying precisely the relationships between theories, models and artifacts. Consequently, we develop a co-des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In recent publications we demonstrated that this method is indeed capable of evaluating thermodynamic observables for magnetic molecules with an accuracy that is nearly indistinguishable from exact results [16,17,18]. So far we encountered only one problem where achieving a satisfying accuracy posed a problem -the Fe III 10 ferric wheel [19]. Mathematically this methods relies on the idea of trace estimators [20]; it is not restricted to spin systems and for instance also applied in quantum chemistry [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent publications we demonstrated that this method is indeed capable of evaluating thermodynamic observables for magnetic molecules with an accuracy that is nearly indistinguishable from exact results [16,17,18]. So far we encountered only one problem where achieving a satisfying accuracy posed a problem -the Fe III 10 ferric wheel [19]. Mathematically this methods relies on the idea of trace estimators [20]; it is not restricted to spin systems and for instance also applied in quantum chemistry [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The different scenario dimensions are acquired from: i) the know-how and real practices of teachers in a problem-based learning approach in a particular framework: an institution IUFM, different categories of probationary teachers, a course about "the air as gas in its static and dynamic aspects: properties, theory and applications"; ii) the theory in didactic anthropology of knowledge of Chevallard [1]; iii) a hierarchical task model. A co-design methodology has been used to articulate teacher real practices, the Chevallard theory and the hierarchical task model to define the different learning system models [7]. The hierarchical task model enables us to define the learning and tutoring activities, the activity distribution among learners, teachers and computers and also to transpose the main concepts of the Chevallard theory.…”
Section: Introductionmentioning
confidence: 99%